Tinjauan Yuridis terhadap Perbuatan Melawan Hukum Pembina Yayasan yang Melakukan Penyalahgunaan Wewenang dalam Pergantian Organ Yayasan - Balhmar, Naflah Lukman; Purwanto, Aldira Mara Ditta Caesar (Universitas Batanghari Jambi, 2024)
The replacement of Foundation Organs is carried out when the term of office of the foundation organ has expired and is not re-elected or when the foundation organ has committed acts deemed detrimental to the foundation by the foundation founder as conducted based on the foundation founder's meeting. If the foundation meeting is not held in accordance with quorum provisions stipulated in the Foundation Law and the Articles of Association, then the founder must be held responsible for his actions. This study was conducted using normative research methods. The results show that the unlawful act committed by the founder in the replacement of foundation organs is the abuse of authority by not adhering to the quorum provisions of the founder's meeting by 2/3 of the founder members, while the responsibility for the unlawful acts refers to civil liability in accordance by Article 1365 of the Civil Code. The legal consequences of such unlawful acts on the foundation organ include the occurrence of dualism in the management of the foundation, the invalidity of decisions made by the newly appointed organ which was unlawfully appointed, and damages to third parties.